We're number one!? - Johnson, Dennis W., author. aut Link Link Link
1 online resource
Keywords: We're Number One!?: America's Uncertain Standing in the World compares the domestic policies of the United States to other countries across a wide variety of social, political, and economic metrics.This book demonstrates conclusively that despite America's wealth, its strong economy, its military might, and its soft power dominance, we have far to go in comparison with other democratic, industrialized nations. We may think we're Number One, but in too many key areas-health care, education, combating poverty, protecting the family, and so forth-we fall embarrassingly short. The shock to most readers won't be on one or more specific policy shortcomings, but on the cumulative rankings, chapter after chapter, showing where the United States has come up short. This book presents the facts and leaves to policymakers the challenge: how do we fix our broken health care system, how do we mitigate climate disasters, or how do we rein in gun violence. One answer is to look at the successful policies created in other countries.A refreshingly frank and thorough analysis of the United States' relative position in the world, this book will appeal to students, scholars, and practitioners of comparative politics, comparative sociology, public policy, social justice, and American government.